Hypothesis paper: high prevalence of Tinel sign in hypermobile Ehlers-Danlos syndrome - Hashemi, Shahreyar Shar; Knight, Dacre R. T. (Frontiers in Neurology, 2025)
Ehlers-Danlos syndromes (EDS) encompass a group of genetic connective tissue disorders that affect the structure and function of proteins and enzymes that provide stability to the body. The hypermobile subtype of EDS (hEDS) is the most common and is characterized by joint hypermobility, skin hyperextensibility, and widespread musculoskeletal pain. Neuropathic symptoms, including pain, numbness, tingling, and weakness, are increasingly recognized in this population. This paper proposes a study to test the hypothesis that hEDS individuals will have a higher prevalence of positive Tinel signs compared to controls, indicating heightened sensitivity to nerve irritation or compression in hEDS that can guide better diagnosis and treatment.